The Sociolinguistics of Iran's Languages at Home and Abroad The Case of Persian, Azerbaijani, and Kurdish - Mirvahedi, Seyed Hadi.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book examines the sociolinguistics of some of Iran's languages at home and in the diaspora. The first part of the book examines the politics of minority languages and the presence of hegemonic discourses which favour Persian (Farsi) in Iran, exploring issues such as language maintenance and shift, linguistic ideologies and practices among Azerbaijani and Kurdish-speaking communities. The authors then go on to examine Iranians' linguistic ideologies, practices and (trans)national identity construction in the diaspora, investigating both the challenges of maintaining a home language and the strategies and linguistic repertoires employed when constructing a diasporic identity away from home. This book will be of interest to students and scholars of minority languages and communities, diaspora and migration studies, and language policy and planning. Seyed Hadi Mirvahedi is a Postdoctoral Fellow in Linguistics and Multilingual Studies at Nanyang Technological University, Singapore. Prior to taking up his fellowship at Nanyang Technological University, he completed his PhD at Victoria University of Wellington, New Zealand.
Chapter 1: Nationalism, modernity and the issue of linguistic diversity in Iran (Seyed Hadi Mirvahedi) -- Part I: The politics of ethnolinguistic diversity in Iran -- Chapter 2: Exploring Azerbaijani speaking parents' linguistic practices and ideologies in Ardebil, Iran (Rasoul Jafari) -- Chapter 3: Linguistic landscaping in Tabriz, Iran: A discursive transformation of a bilingual space into a monolingual place (Seyed Hadi Mirvahedi) -- Chapter 4: Attitudes toward Kurdish in the city of Ilam in Iran (Saeed Rezaei & Ava Bahrami) -- Part II: Iranians abroad: Heritage language use and maintenance -- Chapter 5: Family Language Policy towards Heritage Language Literacy Acquisition and Maintenance: Iranians in New Zealand (Khadijeh Gharibi & Corrine Seals) -- Chapter 6: Mother tongue matters: An ethnographic study of cross-generational voices in negotiation in Farsi mother tongue classes (Narges Ghandchi) -- Chapter 7: 'Are these ones to taste?': Critical Moments in Persian shops in Sydney(Dariush Izadi) -- Part III: Transnational identities and mobility: The role of Persian, ethnic languages, and English -- Chapter 8: Language barrier and internal conflict among Iranian migrants in Australia: A case of unsettling tension (Hossein Shokouhi & Alireza Fard Kashani) -- Chapter 9: Investigating Multilingual Identities and Ideologies among Iranian Communities in Contexts of Mobility (Taraneh Sanei) -- Chapter 10: Mobility, Identity, and Complexity: Iranian Azerbaijanis in the U.S. (Farzad Karimzad) -- Chapter 11: Iranians at home and abroad: Current sociolinguistic issues, possible solutions, and future trajectories (Seyed Hadi Mirvahedi).
Keywords: Sociolinguistics; Multilingualism; Oriental languages; Ethnology -- Middle East .; Culture; Language policy; Linguistic change; Sociolinguistics; Multilingualism; Oriental or Semitic Languages; Middle Eastern Culture; Language Policy and Planning; Language Change